2013
DOI: 10.1186/1475-9276-12-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers in accessing food among recent Latin American immigrants in Toronto

Abstract: ObjectiveIn Canada, recent immigrant households experience more food insecurity than the general population, but limited information is available about the personal, cultural, and social factors that contribute to this vulnerability. This study focused on recent Latin American (LA) immigrants to explore their perceived barriers in acquiring safe, nutritious, and culturally-appropriate food.DesignA cross-sectional mixed-method design was applied to collect information from a convenience sample of 70 adult Spani… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
240
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(262 citation statements)
references
References 23 publications
20
240
1
1
Order By: Relevance
“…Poor level of English language ability is one of the barriers that have been identified in previous studies as having an impact on migrants' ability to access food in an English speaking country (Vahabi & Damba, 2013). However, it was not a major concern for migrants in this study.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Poor level of English language ability is one of the barriers that have been identified in previous studies as having an impact on migrants' ability to access food in an English speaking country (Vahabi & Damba, 2013). However, it was not a major concern for migrants in this study.…”
Section: Discussionmentioning
confidence: 62%
“…Lack of English language skills has been reported in the literature as a reason migrants have difficulty in accessing food (Vahabi & Damba, 2013). Interestingly, most of the interview participants reported they had no problem in communicating and understanding English but the importance of the English language related to the understanding of food information written in English.…”
Section: Language Barriermentioning
confidence: 86%
See 2 more Smart Citations
“…Many studies have demonstrated that food access differs in many countries, including Canada and the US by ethnicity and socioeconomic status (SES) with the lowest access reported in low-income, urban minority neighborhoods and American Indian communities (Lewis et al 2005;Powell et al, 2007a;Larson et al, 2009;Cerin et al, 2011;O'Connell et al, 2011;Fuller et al, 2013;Vahabi & Damba, 2013) and among food stamp recipients (Oberholser & Tuttle 2004;D'Angelo et al 2011). These factors may differ in terms of importance in different cities and countries (Boone-Heinonen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%